The global epidemiology of adolescents living with HIV: time for more granular data to improve adolescent health outcomes. Issue 3 (May 2018) - Slogrove, Amy L.; Sohn, Annette H.
Abstract : Purpose of review: The aim of this study was to summarize recent evidence on the global epidemiology of adolescents (age 10–19 years) living with HIV (ALHIV), the burden of HIV on the health of adolescents and HIV-associated mortality. Recent findings: In 2016, there were an estimated 2.1 million (uncertainty bound 1.4–2.7 million) ALHIV; 770 000 younger (age 10–14 years) and 1.03 million older (age 15–19 years) ALHIV, 84% living in sub-Saharan Africa. The population of ALHIV is increasing, as more peri/postnatally infected ALHIV survive into older ages; an estimated 35% of older female ALHIV were peri/postnatally infected, compared with 57% of older male ALHIV. Although the numbers of younger ALHIV deaths are declining, deaths among older ALHIV have remained static since peaking in 2012. In 2015, HIV-associated mortality was the eighth leading cause of adolescent death globally and the fourth leading cause in African low and middle-income countries. Summary: Needed investments into characterizing and improving adolescent HIV-related health outcomes include strengthening systems for nationally and globally disaggregated data by age, sex and mode of infection; collecting more granular data within routine programmes to identify structural, social and mental health challenges to accessing testing and care; and prioritizing viral load monitoring and adolescent-focused differentiated models of care.